Adaptive path planning for wire-feed additive manufacturing using medial axis transformation. (1st October 2016) - Ding, Donghong; Pan, Zengxi; Cuiuri, Dominic; Li, Huijun; Larkin, Nathan
Abstract: Wire-feed additive manufacturing technologies have made it possible to significantly reduce material waste and energy consumption for fabricating large aerospace metal components that feature high buy-to-fly ratios. This paper presents an innovative path planning strategy using medial axis transformation for the wire-feed additive manufacturing process. The proposed path planning strategy is able to improve geometrical accuracy and produce void-free deposition by continuously altering the deposition width of the wire-feed process to accommodate the component geometry, while simultaneously minimising the number of interruptions to the deposition process at the component boundary. As a result, both buy-to-fly ratio and energy consumption are improved through reducing material waste. The algorithm for generating the adaptive path is described and validated through application to various typical geometries. Buy-to-fly ratios are calculated for a number of thin-walled complex structures. Savings of more than 27% in material usage are achieved using adaptive path planning, when compared with non-adaptive methods. The proposed method is tested experimentally through deposition of two metal components. The results demonstrate that the adaptive strategy is capable of generating void-free deposition with improved accuracy at the component boundary using the wire-feed additive manufacturing process. Highlights: An innovative path planning strategy is presented. High quality (void-free) components can be achieved. Component geometrical accuracy and buy-to-fly ratio are improved. Material waste and energy consumption are reduced by the proposed deposition path.